2020
DOI: 10.1186/s13014-020-01558-8
|View full text |Cite|
|
Sign up to set email alerts
|

Predicting survival in melanoma patients treated with concurrent targeted- or immunotherapy and stereotactic radiotherapy

Abstract: Background: Melanoma patients frequently develop brain metastases. The most widely used score to predict survival is the molGPA based on a mixed treatment of stereotactic radiotherapy (SRT) and whole brain radiotherapy (WBRT). In addition, systemic therapy was not considered. We therefore aimed to evaluate the performance of the molGPA score in patients homogeneously treated with SRT and concurrent targeted therapy or immunotherapy (TT/IT). Methods: This retrospective analysis is based on an international mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Most patients with brain metastases from extracranial primary tumors such as lung or breast cancer receive palliative treatment approaches, because the common pattern of polymetastatic spread may cause compromised performance status (PS) and eventually also limited survival, often in the range of 3–9 months [ 1 ]. Both, longer survival (typically if oligometastases are present [ 2 ]) and shorter survival may be observed, and considerable efforts have been undertaken to predict survival (nomograms, scores, online calculators [ 3 5 ]). Given that very short survival often is synonymous to active treatment in the last 30 days of life, oncologists can opt for palliative and supportive care rather than brain-directed therapy [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Most patients with brain metastases from extracranial primary tumors such as lung or breast cancer receive palliative treatment approaches, because the common pattern of polymetastatic spread may cause compromised performance status (PS) and eventually also limited survival, often in the range of 3–9 months [ 1 ]. Both, longer survival (typically if oligometastases are present [ 2 ]) and shorter survival may be observed, and considerable efforts have been undertaken to predict survival (nomograms, scores, online calculators [ 3 5 ]). Given that very short survival often is synonymous to active treatment in the last 30 days of life, oncologists can opt for palliative and supportive care rather than brain-directed therapy [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent developments in immunotherapy, stereotactic radiosurgery, and fractionated stereotactic radiotherapy have significantly improved the survival rate; the advantage of this type of therapy over holocranial radiotherapy is the preservation of cognitive functions. However, it has been shown that only 25% of patients have access to said combined therapy 4,5 .…”
Section: Discussionmentioning
confidence: 99%
“…Schaule et al conducted a retrospective analysis of 110 patients treated with concurrent targeted or immunotherapy and stereotactic radiotherapy and found that cumulative brain metastases volume (p = 0.04), timing of metastases (syn-versus metachronous) (p = 0.01) and systemic therapy with concurrent immunotherapy (p = 0.005) significantly improved overall survival; with these findings they established a volume-timingsystemic therapy (VATS) score with point values ascribed to the aforementioned factors and median overall survival as of 34.5 months in patients with a VATS score of 2 (p = 0.03) (70).…”
Section: Melanomamentioning
confidence: 92%